Risk Factors Associated with Morbidity and Mortality after Cervical Spine Injury at Dr Sardjito General Hospital - Nashiruddin, Nashiruddin; Fajar Apsari, Ratih Kumala; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: Cervical injury is a form of spinal cord trauma with high morbidity and mortality rates, especially in developing countries. Identifying risk factors is essential for prevention strategies, management, and improved patient outcomesObjective: This study aims to observe the effect of listening to music on the anxiety level of surgical patients undergoing subarachnoid block anesthesia. To analyze risk factors of cervical injury related to morbidity and mortality, and to present the demographic profile of cervical injury cases at Dr Sardjito General HospitalMethods: This study employed a retrospective case-control design involving 127 patients with cervical injury treated at Dr Sardjito General Hospital, Yogyakarta, from January 1, 2022, to December 31, 2024. Data were collected from medical records and analyzed using bivariate analysis (Fisher’s exact test). A p-value <0.05 was considered statistically significant.Results: The majority of patients were male (88.2%) with an average age of 50.57 years. The most common trauma mechanisms were falls from height (45.7%) and traffic accidents (44.9%). Severe disability as morbidity was experienced by 41.7% of patients, while mortality reached 31.5%. Risk factor analysis for morbidity did not find any variables significantly associated with clinical outcomes (P>0.05). Length of stay (LOS) was significantly associated with morbidity (p=0.001). Significant risk factors for mortality included respiratory comorbidity (OR 4.50; p=0.004)Conclusion: ASIA score, prolonged ventilator use, and tracheostomy were identified as risk factors for mortality in cervical injury patients at Dr Sardjito General Hospital. No statistically significant risk factors were found to be associated with morbidity